Non-Destructive Inspection of Mango Fruit Using Digital Radiography, Computed Tomography and Magnetic Resonance Imaging - Kalne, Abhimannyu; Kotwaliwale, Nachiket; Singh, Karan; Singh, Vijay Kumar (Journal of Agricultural Engineering, 2013)
Presence of seed weevil, internal physiological disorders and spongy tissues are undesirable internal features that are often found in mangoes. Fruits affected by these defects many times do not show any external symptom, and thus it is extremely difficult to sort out undesired fruits. Some major varieties of Indian mangoes were collected from different parts of India and digital images were generated using soft X-ray radiography, computed tomography (CT) and magnetic resonance imaging (MRI). Acquired images of fruits could be successfully used to differentiate healthy and defected fruits. Dark patches and irregular tissue patterns were prominently observed in defective fruits, while healthy fruits’ images showed uniform light grayness in the pulp part. It was also seen that the anomalies visible in digital images (radiograph, CT and MRI) represented the actual defects visible in physically cut cross-section mages. X-ray, CT and MR imaging techniques have a good potential to detect infested mangoes nondestructively, and can be further applied in processing industry and in export trade as a quality inspection tool, thereby improving the quality of mango fruits sent for market or export.